Primary school students' mathematical literacy in solving multiple-solution - Sri Nur Wahyu Utami; Mohammad Faizal Amir (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2023)
This study aims to analyze primary school students' mathematical literacy (ML) in solving multiple-solution (MS) problems. We call students ML to solve MS with MS-ML. The research subjects are students from grade four in a Sidoarjo, East Java primary school. The research method used is descriptive qualitative with a case study approach. The instruments used were an MS-ML test and an interview. Interviews were conducted with several students who were selected through the MS-ML category. There are three indicators of MS-ML: the formulating stage, the employing stage, and the interpreting stage. The results of the analysis showed that there were appropriate and inappropriate MS-ML categories. Most students are in the inappropriate MS-ML category. Many students struggle to formulate, employ, and interpret the correct divergent solution. We suggest that one familiarize oneself with divergent ML-MS-based problem-solving in learning and teaching, namely building ML problem-solving with multiple solutions or MS strategies.